تعليم البلاغة من خلال الأساليب البلاغية لأحاديث أدب الطالبين لترقية مهارة الكتابة على طلبة قسم اللغة العربية وأدبها بجامعة سونن أمبيل الإسلامية الحكومية سورابايا - Mufaizah, Mufaizah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2017)
Writing is a kind of important skills. Moreover, writing skill is one of the main objectives in learning foreign language. However, students’ skill is still lowgrade in this writing skill. The condition of this lowgrade is not caused by the difficulty of foreign language writing but it is caused of the ineffective and unsupportive teaching tools and teaching media. The purposes of this study are: 1) to train the university students in developing of writing using simple and pleased sentences and also systematic structure. 2) to assist the university students in revision, editing, and correcting the articles. 3) to improve the university students’ skill in Arabic writing skill. This study applied qualitative and quantitative research especially experimental research in writing skill during teaching learning process using al-Asalib al-Balaghiyyah media. This teaching style consists of 4 levels. They are planning, action, observation, and reflection. Research data are from lecturers’ and university students’ activities during teaching learning process of writing skill and the university students’ articles of Arabic Classes Special Program in Islamic State University of Sunan Ampel, Surabaya especially semester 2, Class E and F.